Xylella fastidiosa subsp. pauca, Neofusicoccum spp. and the Decline of Olive Trees in Salento (Apulia, Italy): Comparison of Symptoms, Possible Interactions, Certainties and Doubts - Marco Scortichini; Giuliano Manetti; Angela Brunetti; Valentina Lumia; Lorenzo Sciarroni; Massimo Pilotti (Plants, 2023)
Xylella fastidiosa subsp. pauca (XFP), Neofusicoccum mediterraneum, N. stellenboschiana and other fungi have been found in olive groves of Salento (Apulia, Italy) that show symptoms of severe decline. XFP is well known to be the cause of olive quick decline syndrome (OQDS). It has also been assessed that Neofusicoccum spp. causes a distinct disease syndrome, namely, branch and twig dieback (BTD). All these phytopathogens incite severe symptoms that can compromise the viability of large canopy sectors or the whole tree. However, their specific symptoms are not easily distinguished, especially during the final stages of the disease when branches are definitively desiccated. By contrast, they can be differentiated during the initial phases of the infection when some facets of the diseases are typical, especially wood discoloration, incited solely by fungi. Here, we describe the typical symptomatological features of OQDS and BTD that can be observed in the field and that have been confirmed by Koch postulate experiments. Similar symptoms, caused by some abiotic adverse conditions and even by additional biotic factors, are also described. Thus, this review aims at: (i) raising the awareness that declining olive trees in Salento do not have to be linked a priori to XFP; (ii) defining the guidelines for a correct symptomatic diagnosis to orient proper laboratory analyses, which is crucial for the application of effective control measures. The possibility that bacterium and fungi could act as a polyspecies and in conjunction with predisposing abiotic stresses is also widely discussed.